Risk of malnutrition and health-related quality of life in community-living elderly men and women : the Tromsø study. - Kvamme, Jan-Magnus; Olsen, Jan Abel; Florholmen, Jon; Jacobsen, Bjarne Koster (Quality of Life Research, 2011)
Purpose To explore the association between risk of malnutrition as well as current body mass index (BMI) and health-related quality of life (HRQoL) in elderly men and women from the general population. Methods In a cross-sectional population survey including 1,632 men and 1,654 women aged 65 to 87 years from the municipality of Tromsø, Norway, we assessed HRQoL by using the EuroQol (EQ-5D) instrument in three risk groups of malnutrition and in different categories of BMI. The Malnutrition Universal Screening Tool (‘MUST’) was used to evaluate the risk of malnutrition. Results We found a significant reduction in HRQoL with an increasing risk of malnutrition, and this was more pronounced in men than in women. The relationship between BMI and HRQoL was dome shaped, with the highest score values in the BMI category being 25–27.5 kg/m2. Conclusions HRQoL was significantly reduced in elderly men and women at risk of malnutrition. The highest HRQoL was seen in moderately overweight individuals.